Targeted therapy for the treatment of gliomas with multifunctional orange emissive carbon dots. Issue 3 (13th January 2022) - Liu, Shuyao; Zhong, Zhuoling; Zhang, Chuanwei; Zhou, Yanqu; Fu, Chunmei; Xu, Xiaoping
Abstract : As a nano-material, carbon dots have been extensively studied and applied in many ways. Abstract : As a nano-material, carbon dots have been extensively studied and applied in many ways. Herein, iron-doped orange emissive carbon dots (ICDs) were easily synthesized using the hydrothermal method and coupled with Trf and glucose oxidase (GOD) simply by virtue of the abundant functional groups on their surface. The resulting carbon dots were named IGTCDs. The obtained IGTCDs possessed targeting, therapeutic and imaging functions, achieving the enzymolysis of glucose, the decomposition of H2 O2 and the release of reactive oxygen species (ROS) sequentially in gliomas as a multifunctional nano-catalyst, and achieving an efficient glioma targeted killing effect. On the basis of the ideal biocompatibility of the IGTCDs with a cell survival rate of over 85%, even at a high concentration (500 μg ml −1 ), the IGTCDs, which were coupled substances present within the organism, glucose oxidase and transferrins, showed an obvious inhibitory effect on the growth of tumor cells, and the survival rate of the C6 cells was only 28.10% at 300 μg ml −1 . The highly efficient anti-tumor effect was further demonstrated in the treatment of mice suffering from glioma, and the tumor inhibition rate was increased to 56.21–98.32%. This safe and effective multifunctional tumor inhibitor could be conveniently synthesized in large quantities, verifying the feasibility of the anti-tumor therapy based on the tumor microenvironment (TME), creating a novel method for the application of carbon dots in tumor treatment and providing a novel, reasonable and effective method for the treatment of cancer and gliomas.